Increased expression of retinoic acid-induced gene 1 in the dorsolateral prefrontal cortex in schizophrenia, bipolar disorder, and major depression - Haybaeck J (Dove Medical Press, 2015)
Johannes Haybaeck,1 Magdalena Postruznik,1 Christine L Miller,2 Jeannette R Dulay,3 Ida C Llenos,3,4 Serge Weis3,4 1Department of Neuropathology, Institute of Pathology, Medical University Graz, Graz, Austria; 2Department of Pediatrics, Johns Hopkins University, Baltimore, 3Laboratory of Brain Research and Neuropathology, Departments of Psychiatry and Pathology, Uniformed Services University of the Health Sciences, and Stanley Medical Research Institute, Bethesda, MD, USA; 4Laboratory of Neuropathology, Department of Pathology and Neuropathology, State Neuropsychiatric Hospital Wagner-Jauregg, Medical School, Johannes Kepler University, Linz, Austria Background: Retinoids regulate gene expression in different cells and tissues at the transcriptional level. Retinoic acid transcriptionally regulates downstream regulatory molecules, including enzymes, transcription factors, cytokines, and cytokine receptors. Animal models indicate an involvement of retinoid signaling pathways in the regulation of synaptic plasticity and learning, especially in the hippocampus. Retinoic acid-inducible or induced gene 1 (RAI-1) is induced during neuronal differentiation, and was associated with the severity of the phenotype and response to medication in schizophrenic patients. Methods: In the present study, we used immunohistochemistry to investigate the expression of RAI-1 in 60 brains from the Stanley Neuropathology Consortium (15 cases each from controls and from patients with schizophrenia, bipolar disorder, and major depression). Rating scores for density and intensity were determined in the dorsolateral prefrontal cortex. Results: All four groups showed high interindividual variation. RAI-1-positive cells were identified as neurons and astrocytes. Significantly increased intensities in cortical neurons were noted in all three major psychiatric groups compared with controls. The density of RAI-1-positive neurons was increased (P=0.06) in schizophrenia and bipolar disorder. In bipolar disorder, RAI-1-positive astrocytes in gray matter showed a significantly increased intensity and compound value. Thus, a significant increase in the parameters measured was found in schizophrenia, bipolar disorder, and major depression. Conclusion: Our study shows a significant increase in expression of RAI-1 in the brains from patients with schizophrenia, bipolar disorder, or major depression. The increased expression might reflect altered signaling pathways, like that for retinoic acid. The underlying mechanisms leading to the increased expression and its functional consequences are so far unknown, and remain to be investigated in future studies. Keywords: retinoic acid-inducible gene 1, dorsolateral prefrontal cortex, schizophrenia, bipolar disorder, major depression